Unsteady Compressible Stokes Layers on a Disk - Murthy, K.N. Venkatasiva (Defence Science Journal, 2014)
The unsteady motion of a viscous compressible rotating gas bounded by a single infinite disk is studied when small amplitude torsional oscillations are superimposed on the disk. The generation and propagation of waves due to the interactions of compressibility, viscosity and rotation during the transient evolution is discussed. In comparison with the non-oscillatory case, the forcing frequency of the disk is capable of inducing several additional interesting features.